EFEKTIVITAS PROGRAM VAKSINASI RETROVIRUS DAN PCV DI UPTD PUSKESMAS II DINAS KESEHATAN KECAMATAN DENPASAR TIMUR - UNILAWATI, PUTU; Widanti, Ni Putu Tirka; Utari, Nyoman Diah (Jurnal Widya Publika, 2024)
The vaccination program was a national and international program designed to control the morbidity and mortality rates of various diseases. In providing the Retrovirus and PCV vaccination program, UPTD Puskesmas II East Denpasar District Health Service will refer to Decree Number 445/06/Pusk.II.DT/2023 concerning types of services at UPTD Puskesmas II East Denpasar District Health Service related to the vaccination program Retroviruses and PCV. There are problems related to the effectiveness of the Retrovirus and PCV vaccination program at UPTD Puskesmas II, East Denpasar District Health Service, this condition is the background for this research in order to find out what obstacles and strategies are being implemented to increase the effectiveness of the Retrovirus and PCV vaccination program at UPTD Puskesmas II, East Denpasar District Health Service. This research uses a qualitative descriptive method approach by observation and interview. The objective of this research is to determine and analyze the obstacles and strategies implemented in increasing the effectiveness of the Retrovirus and PCV vaccination program at UPTD Puskesmas II, East Denpasar District Health Service. The results of the research show that the Retrovirus and PCV vaccination program at UPTD Puskesmas II, East Denpasar District Health Service, seen from indicators of goal achievement and integration, is not yet fully effective, but seen from adaptation it is already effective. The obstacle is that there has not been comprehensive socialization. The strategy carried out is the need to collaborate with cadres and cross-sectors in socializing the Retrovirus and PCV vaccination program to the community and targeting areas with indications of diarrhea or pneumonia to receive Rotavirus and PCV vaccinations.